2011
DOI: 10.1002/mrm.22957
|View full text |Cite
|
Sign up to set email alerts
|

Study on metabonomic characteristics of human lung cancer using high resolution magic‐angle spinning 1H NMR spectroscopy and multivariate data analysis

Abstract: Lung cancer causes serious health problems. Clinical diagnosis of lung cancer relies on histopathological evalution of tissue specimen. However, extensive knowledge of the metabolic biochemistry of tumors can potentially provide important information for accurate diagnosis of lung cancer. High resolution magic-angle spinning NMR spectroscopy has emerged and be widely acknowledged as an excellent tool in investigating tissue metabolism. Moreover, the combination of high resolution magic-angle spinning NMR techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 34 publications
3
27
0
Order By: Relevance
“…The main aim of these studies was to reveal metabolic differences between healthy and cancerous tissue and to use these results as a tool for disease discrimination. Results showed that Lac, ChoCCs, and Tau were consistently elevated in cancer, whereas Glc, acetate, myo −/ scy ‐Ino, and Gly were found to be decreased . As previously discussed, the decrease in Glc and increase in Lac is likely linked to the Warburg effect, and the higher levels of ChoCCs are markers for cell proliferation.…”
Section: Applications Of Hrmas Mrs In Studies Of Human Malignant Disesupporting
confidence: 53%
See 1 more Smart Citation
“…The main aim of these studies was to reveal metabolic differences between healthy and cancerous tissue and to use these results as a tool for disease discrimination. Results showed that Lac, ChoCCs, and Tau were consistently elevated in cancer, whereas Glc, acetate, myo −/ scy ‐Ino, and Gly were found to be decreased . As previously discussed, the decrease in Glc and increase in Lac is likely linked to the Warburg effect, and the higher levels of ChoCCs are markers for cell proliferation.…”
Section: Applications Of Hrmas Mrs In Studies Of Human Malignant Disesupporting
confidence: 53%
“…Further, PCA and cross‐validated OPLS‐DA approaches were used to create a differentiation tool based on HRMAS MRS data. PCA could discriminate between the different sample origins—center, parenchyma, adjacent—and OPLS‐DA differentiated Stage I/II from III/IV and AC from SCC (Figure ) …”
Section: Applications Of Hrmas Mrs In Studies Of Human Malignant Disementioning
confidence: 99%
“…Metabolic ratios of glycerophosphocholine (GPCho), phosphocholine/creatine (Pcho/Cr), myo-inositol/scyllo-inositol, choline/creatine (Cho/Cr) and other ratios were found to correlate with the number of tumor cells, tumor cell proliferation, and (for non-malignant tissue) the distance to the nearest tumor (Cheng et al, 2005). 1 H MR has been used to study the metabolic status of human tumors with examples that include brain (McKnight, 2004a,b), gastric (Jung et al, 2014), rectal (Wang et al, 2013), renal (Süllentrop et al, 2012), lung (Chen et al, 2011), bladder (Srivastava et al, 2010), ovarian (McLean et al, 2009), breast (Haddadin et al, 2009), cervix (Mahon et al, 2004), kidney (Tate et al, 2000), adipose tissue (Chen et al, 2002) and other types of tissues (Tugnoli et al, 2006). 1 H MRS can have a clinical impact providing detailed information on changes in all observed tissue metabolites simultaneously.…”
Section: H Magnetic Resonancementioning
confidence: 97%
“…Metabonomics provides a systematic, time-dependent measurement of metabolic shifts occurring in response to drugs, environmental stimuli or disease [19][20][21][22][23][24][25][26][27][28][29]. It offers a functional view of system activity by showing all micromolecular data downstream of the genome and proteome [30].…”
Section: Metabolic Biomarkersmentioning
confidence: 99%
“…It offers a functional view of system activity by showing all micromolecular data downstream of the genome and proteome [30]. This wider view of system activity past macromolecules such as DNA and RNA could facilitate personalized approaches for colorectal cancer diagnosis, prognosis and therapeutic personalisation [22,28].…”
Section: Metabolic Biomarkersmentioning
confidence: 99%